2016
DOI: 10.3389/fnagi.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Prepulse Inhibition and Startle Reflex by Emotions: A Comparison between Young and Older Adults

Abstract: This study examined whether or not the acoustic startle response and sensorimotor gating may be modulated by emotions differentially between young and older adults. Two groups of participants (mean age Young: 24 years old; Elderly: 63.6 years old) were presented with three types of auditory stimuli (Startle alone, High or Low frequency Prepulse) while viewing pleasant, neutral, or unpleasant images. Electromyographic activity of the eyeblink response was measured. Results show that older adults displayed dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…Some findings overturn basic assumptions in the field and make it obvious how little we really understand. In my opinion, findings by Le Duc et al ( 2016 ) regarding age differences in how emotional stimuli influence startle reactivity fit this profile. They found age differences in how viewing pleasant, unpleasant and neutral pictures modulated a startle response to a loud noise (Figure 1A ).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Some findings overturn basic assumptions in the field and make it obvious how little we really understand. In my opinion, findings by Le Duc et al ( 2016 ) regarding age differences in how emotional stimuli influence startle reactivity fit this profile. They found age differences in how viewing pleasant, unpleasant and neutral pictures modulated a startle response to a loud noise (Figure 1A ).…”
supporting
confidence: 52%
“… Age-by-valence interactions in startle reactivity from (A) Le Duc et al ( 2016 ); and (B) Feng et al ( 2011 ) . …”
mentioning
confidence: 99%
“…It is likely that the differences in the procedure employed to induce the affective state are responsible for some of the apparently contradictory results, since the remaining parameters used to record PPI are highly standardized (Geyer & Swerdlow, 1998), which makes it less likely that the differences were due to these parametric factors. Most of the studies in this field have presented IAPS images (Bradley & Lang, 2007) to induce the affective states (e.g., De la Casa et al, 2016, Experiment 1; Hawk & Kowmas, 2003), and none of these studies found a reduction in PPI (but see, Le Duc et al, 2016 that found a significant reduction in PPI for Young adults participants exposed to negative pictures, and a significant increase in PPI for older adults exposed to positive pictures). It is possible that presenting pictures of loved familiar faces was a more effective procedure for generating an intense positive affective response capable of disrupting PPI.…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced sensorimotor gating can be explained from the model proposed by Schmajuk et al (2009) proposing that increased dopamine transmission in Ventral Tegmental Area will inhibit the process responsible of PPI. However, previous experiments analyzing the effect of different affective states on PPI evidenced a complex pattern of results – for instance, enhanced PPI in elderly adults when a positive affect was induced, and reduced PPI in young adults when the induced affect was negative (Le Duc et al, 2016). Until the nature of these discrepancies is elucidated, future research should take into account differences in age and, particularly, in the procedure employed to induce the affective state in the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation